Islamic republic of Iran - Wan, Chang Da; Russayani Ismail; Lai, Yew Meng; Zainal Amin Ayub; Abdul Razak Ahmad (Springer Science+Business Media Singapore 2016, 2016)
The Islamic Republic of Iran is an important and interesting case study to understand in the context of higher education development in the MENA region. The Iranian higher education system can be considered as among the most developed in the region, especially in research and development, despite economic sanctions. With the lifting of the sanctions and having possessed rich economic resources as well as coupled by a relatively stable political situation, these have brighten the prospects for the development of the Iranian higher education. This chapter examines the challenges and prospects of higher education in Iran as well as from the politico-security, economic, social, legal, and educational perspectives as a means to develop holistic insights of higher education in a post-sanction Iran and the MENA region.